[Dicyclohexyl(sulfanylidene)-λ5-phosphanyl]methanol - Henderson, William; Okpareke, Obinna C.; Ainnul H. S. Azizan, *; Tiekink, Edward R. T. * (MDPI, 2019)
The title compound, [dicyclohexyl(sulfanylidene)-λ5 -phosphanyl]methanol, Cy2P(=S)CH2OH (1), was obtained from the reaction between [Cy2P(CH2OH)2]Cl with one molar equivalent of NaOH and an excess of elemental sulfur (powdered). Characterization was by a single-crystal X-ray structure determination as well as IR, and 1D-NMR (1H,13C{1H}, 31P{1H}), and 2D-NMR (DEPT-135 and HSQC) spectroscopy, ESI mass spectrometry, and elemental analysis. X-ray crystallography on Compound 1 shows the phosphorus atom to be tetrahedrally coordinated within a non-symmetric C3S donor set but with relatively minor distortions from the ideal geometry. In the molecular packing, hydroxyl-O–H· · · S(thione) hydrogen bonds led to supramolecular helical chains along the b-axis direction.